Optimal linear control to parametric uncertainties in a micro electro mechanical system - Chavarette, F́abio Roberto [UNESP] (Academic Publications, 2013)
This paper, a micro-electro-mechanical systems (MEMS) with parametric uncertainties is considered. The non-linear dynamics in MEMS system is demonstrated with a chaotic behavior. We present the linear optimal control technique for reducing the chaotic movement of the micro-electromechanical system with parametric uncertainties to a small periodic orbit. The simulation results show the identification by linear optimal control is very effective. © 2013 Academic Publications, Ltd.
Keywords: Chaos control; Linear optimal control; Micro electro mechanical system